(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Patients with diabetes have an increased risk of developing microvascular complications, diabetic retinopathy, diabetic nephropathy and diabetic neuropathy, which if not predicted, early detected and treated, place a significant burden on individual’s health and can reduce life expectancy. Objective:To determine the main risk factors (predictors) that associated with microvascular complications in diabetes aiming to construct a module that can detect microvascular complications depending on these predictors. Methods: A cross sectional descriptive study was carried out with 364 diabetic patients. Data about diabetes microvascular complications (retinopathy, clinical peripheral neuropathy, and nephropathy) and their potential risk factors were collected. Primary point was detecting the < 0.01 level of significant association of risk factors with these complications to determine the predictors. These predictors were assessed for each individual’s micro vascular complication and also as a composite outcome by logistic regression analysis. Result:Of the examined 364 diabetic cases, 174 (47.80%) patients were found with microvascular complications. Neuropathy, nephropathy, and retinopathy were detected in 66 (18.13%), 62 (17.03), and 46 (12.64%) patients, respectively. Out of 12 potential predictors, only six (age, smoking habit, duration of diabetes, uncontrolled hyperglycemia, hypertension, and macrovascular complications) found to be significantly associated with the presence of microvascular complication (p < 0.01) as compared with patients who had no such complications. Uncontrolled hyperglycemia was the first predictor in neuropathy and nephropathy groups, while diabetic duration was ranking first in retinopathy group. Conclusions: Microvascular complications in diabetic patients can be predicted, and avoided, by detecting their risk factors. Logistic regression equation provide suitable module for evaluation of these risk factors simultaneously. Key words: Microvascular complications, diabetes, logistic regression